Integrated Hydrological Modeling and Spatial Analysis for Flash Flood Risk Assessment: A Comprehensive Case Study of Aden Governorate, Yemen (The International Journal for Scientific Research, 2026)
This comprehensive study provides an in-depth evaluation of flash flood hazards in Aden Governorate, Yemen, a region characterized by complex volcanic topography and rapid, often unregulated, urban expansion. Utilizing the Watershed Modeling System (WMS 11.0) and Geographic Information Systems (GIS), the research analyzes 15 primary drainage basins across the districts of Sirah, Al-Mualla, Al-Tawahi, and Al-Buraiqa. The study employs the HEC-1 hydrological model to simulate flood hydrographs and estimate peak discharges for return periods ranging from 5 to 100 years. Land Use and Land Cover (LULC) analysis using Sentinel-2 imagery (2017–2023) reveals an 82% increase in built-up areas, significantly altering the hydrological response of the watersheds. The results indicate extreme peak discharges, reaching up to 9,272 m³/s for Wadi Al-Kabir and 257.94 m³/s for Wadi Al-Khasaf during a 100-year event. Spatial inundation mapping identifies critical risk zones in Al-Qati’, Souq Al-Baz, and Al-Haswa, where water levels could reach up to 3 meters. The study proposes a multi-tiered mitigation strategy, integrating structural interventions such as check dams and drainage rehabilitation with non-structural measures like early warning systems and strict zoning enforcement. This research serves as a critical blueprint for sustainable urban flood management in arid coastal cities.
Keywords: Flash Flood Risk; Hydrological Modeling; WMS; HEC-1; GIS; Aden Governorate; Urban Resilience